2014
DOI: 10.1073/pnas.1322085111
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid sensor RCAR7/PYL13, specific regulator of protein phosphatase coreceptors

Abstract: The plant hormone abscisic acid (ABA) acts both as a developmental signal and as an integrator of environmental cues such as drought and cold. ABA perception recruits an ABA-binding regulatory component [regulatory component of ABA receptor (RCAR)/ PYR1/PYL] and an associated protein phosphatase 2C (PP2C). Phytohormone binding inactivates the phosphatase activity of the coreceptor, permitting phosphorelay of the ABA signal via downstream protein kinases. RCARs and PP2C coreceptors are represented by small prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 49 publications
2
56
0
1
Order By: Relevance
“…In the same context, selective discrimination of PP2Cs by specific RCARs such as RCAR7/PYL13 point to RCAR-specific features. In fact, analysis-of-specificity determinants for RCARs (30,33,45,46) and PP2C HAB1 (32) and AHG1 (this study) showed that both receptor components have evolved key-lock features. RCAR7 did not rescue ABI1-, AHG1-, and HAB1-inhibited ABA signaling in this study in agreement with previous analyses (32,35).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In the same context, selective discrimination of PP2Cs by specific RCARs such as RCAR7/PYL13 point to RCAR-specific features. In fact, analysis-of-specificity determinants for RCARs (30,33,45,46) and PP2C HAB1 (32) and AHG1 (this study) showed that both receptor components have evolved key-lock features. RCAR7 did not rescue ABI1-, AHG1-, and HAB1-inhibited ABA signaling in this study in agreement with previous analyses (32,35).…”
Section: Discussionmentioning
confidence: 67%
“…In fact, analysis-of-specificity determinants for RCARs (30,33,45,46) and PP2C HAB1 (32) and AHG1 (this study) showed that both receptor components have evolved key-lock features. RCAR7 did not rescue ABI1-, AHG1-, and HAB1-inhibited ABA signaling in this study in agreement with previous analyses (32,35). Characterization of the RCAR7-specific repulsion by HAB1 revealed that changes in two amino acid residues of HAB1 located at the RCAR interaction surface confer RCAR7 binding and regulation (32).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This implies a fine adjustment of the magnitude of the physiological response and requires a more complex regulatory system than the sole presence/absence of ABA. Indeed, there are 14 loci encoding for ABA receptors in Arabidopsis, each of them having different intrinsic affinities for the hormone and could also bind to specific PP2Cs (Dupeux et al 2011;Santiago et al 2012;Antoni et al 2013;Fuchs et al 2014). Besides the fine-tuning of the ABA signal, modulation of the endogenous hormone levels is associated to the specific environmental situation and the stress pressure, which adds further complexity to the model (Seiler et al 2011;Romero et al 2012b; Baron et al 2012;De Ollas et al 2013).…”
Section: Introductionmentioning
confidence: 99%